2015
DOI: 10.1093/annonc/mdu543
|View full text |Cite
|
Sign up to set email alerts
|

Intensive follow-up strategies improve outcomes in nonmetastatic colorectal cancer patients after curative surgery: a systematic review and meta-analysis

Abstract: Intensive follow-up strategies improve overall survival, increase the detection of asymptomatic recurrences and curative surgery attempted at recurrence, and are associated with a shorter time in detecting recurrences. This more intensive follow-up could not be associated with an improvement in cancer-specific survival nor with an increased detection of total tumor recurrences. Follow-up with serum carcinoembryonic antigen and colonoscopies are related to an increase in overall survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
178
1
8

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 222 publications
(187 citation statements)
references
References 38 publications
0
178
1
8
Order By: Relevance
“…16 Two meta-analyses have also supported the use of 1-year follow-up colonoscopies. 4,29 Despite the fact that most guidelines recommend 1-year follow-up surveillance colonoscopy, we found that nonadherence was substantial. Four other studies conducted in large population-based administrative databases found comparable results.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…16 Two meta-analyses have also supported the use of 1-year follow-up colonoscopies. 4,29 Despite the fact that most guidelines recommend 1-year follow-up surveillance colonoscopy, we found that nonadherence was substantial. Four other studies conducted in large population-based administrative databases found comparable results.…”
Section: Discussionmentioning
confidence: 67%
“…The rationales for these recommendations stem from observational studies and clinical trials that have shown improved progression-free and overall survival rates for those found to have liver or lung metastases who have undergone metastasectomies. 4,5 The guidelines [1][2][3]6 also recommend a surveillance colonoscopy at 1 year following surgery. This has two goals: to remove metachronous lesions which may arise rapidly after the initial resection or which may represent missed lesions; [7][8][9][10][11] and to identify anastomotic recurrences which may develop in up to 4% of patients.…”
Section: Introductionmentioning
confidence: 99%
“…A recent systematic review concluded that intensive follow-up strategies were associated neither with improved cancer-specific survival, nor with a higher detection rate for tumour recurrences after curative treatment of CRC [9]. The FACS-trial, the most recent randomized controlled trial comparing multiple follow-up strategies with the same intensity but different components, suggested that follow-up should include at least one of the 2 components, CEA or imaging [3].…”
Section: Introductionmentioning
confidence: 99%
“…That study showed no difference in time to detection of recurrence, OS, or quality of life assessments at any interval between the stage-matched cohorts [23]. Multiple randomized trials and separate meta-analyses support a modest but significant OS benefit for intensive posttreatment surveillance following potentially curative resection of colorectal cancer [24-27]. However, the best surveillance strategy to achieve such a benefit has not been defined because the strategies within trials varied significantly.…”
Section: Discussionmentioning
confidence: 99%